2013
DOI: 10.5546/aap.2013.eng.115
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the risk of microbiological contamination between samples of breast milk obtained at home and at a healthcare facility

Abstract: Introduction. Breast milk is the best food for preterm infants. Due to their inadequate suction-swallowing action, the administration of expressed breast milk should be done with an orogastric tube. There is little information available regarding the microbiological safety of expressed breast milk. The aim of this article was to evaluate if there were any differences regarding the contamination of breast milk obtained at a healthcare facility versus at home. Methods. Cross-sectional study that analyzed pairs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
1
11
0
5
Order By: Relevance
“…The clean collection of expressed breast milk is crucial to obtain milk with very little bacteria, as it has an impact on acceptable storage duration . Collecting human milk in neonatal units was shown to significantly reduce the risk of microbial contamination when it was compared to home collection . The guidelines for the collection and handling of breast milk must be followed, both at the hospital and at home .…”
Section: Resultsmentioning
confidence: 99%
“…The clean collection of expressed breast milk is crucial to obtain milk with very little bacteria, as it has an impact on acceptable storage duration . Collecting human milk in neonatal units was shown to significantly reduce the risk of microbial contamination when it was compared to home collection . The guidelines for the collection and handling of breast milk must be followed, both at the hospital and at home .…”
Section: Resultsmentioning
confidence: 99%
“…Differences in the impact of context on cleaning and disinfection methods for handling EBM were discussed in two studies. 52,54 One paper that was cited in a literature review described differences in contamination levels between hospitals and homes and found that EBM expressed at home was more contaminated. 54 Serra and colleagues' study corroborated this finding.…”
Section: Expression Methodsmentioning
confidence: 98%
“…54 Serra and colleagues' study corroborated this finding. 52 standards. 12 The UK's NHS had clear recommendations for feeding equipment cleaning methods.…”
Section: Expression Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This microorganism is common in regions of the human body such as the nasal passages, throat, skin, and hair (Silva et al, 2010). According with Serra et al (2013), the presence of pathogenic bacteria such as Staphylococcus aureus, Escherichia coli, Streptococcus faecalis, Enterobacter sakazakii, (â-hemolytic) Streptococcus pyogenes, species of Pseudomonas, Proteus and Salmonella is considered unacceptable for food or human milk. Table 1.…”
Section: Hygienic-sanitary Quality Of Milkmentioning
confidence: 99%